Karakteristik Intensitas Radioaktivitas Batuan dan Sedimen Terpilih di Pantai Sedau, Kalimantan Barat - Aryanto, Noor Cahyo Dwi; Sarmili, Lili; Suparka, Emmy; Permana, Haryadi (BRIN Publishing, 2015)
The intensity of the radioactive elements based on the rock activity data and ß powder emission activity on Sedau Coast were done using Gamma Spectrometer analysis method and ß detector to the nine samples of sediment and rocks. Radioactive intensity of U238 in rocks showed a range from 0.1202 ± 0.008 Bq/ 25gr to 0.4348 ± 0.005 Bq/ 25gr; Th232 0.0768 ± 0.005 Bq/ 25gr to 0.4812 ± 0.015 Bq/ 25gr; while the gross gamma intensity ranged from 1.0503 ± 0.029 Bq/ 25gr to 5.6433 ± 0.273 Bq/25gr. All the sample that has high intensity of radioactive element, occurs in the same rock (monzogranite) which is from samples in location SKP08-04. The same results in the emission of ß powder, which showed the highest gross ß activity also occurs in the rocks monzogranite (SKP08-04) with exposure intensity was 0.370 ± 0.025 Bq/25gr. Based on petrographic observations, monzogranite in SKP08-04 showed the presence of abundant feldspar with the condition which relatively not altered, whereas the affinity based on geochemical analysis showed a calc-alkaline series of high potassium.